Rancang Bangun Sistem Informasi Pengelolaan Inventory Berbasis Website Menggunakan Metode ROP dan EOQ (Studi Kasus: Grosir PA1000 RAJA) - Yuli Fitrisia; Mardhiah Fadhli; Jordan Abeth Teofilus Pasaribu (Jurnal Komputer Terapan, 2022)
Wholesale PA1000 RAJA is a wholesaler with its address at Batang Kumu II, Rokan Hulu, Riau and has been around for about 9 years. This PA1000 RAJA wholesaler is still recording sales and inventory manually with a book, so that there is often a shortage of goods when ordered by customers or too many goods in the warehouse. Based on the existing problems, a website-based information system was created to manage the existing inventory at the wholesaler. In making this information system applies the ROP method as a form if the inventory is below the minimum limit, then there is a warning so that the wholesaler reorders goods that have been exhausted. After knowing the amount of stock, the Economic Order Quantity (EOQ) method is needed to find out how much the economic quantity of goods that must be ordered. Based on the results of the User Acceptance Test (UAT) which was carried out 3 times, it was stated that all user needs had been met as a whole.